(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Management of risks in the infrastructure projects has been categorized of utmost importance to the process of management so that the project objectives and motives in terms of time, cost, quality may be accomplished. The identification and analysis of risks which are bracketed with infrastructure projects is the main aim of this paper. Risks have been identified and classified in this paper based on comprehensive assessment of conditions of contracts. It has been seen that the project objectives are impacted heavily due to the opposition of social bodies, the qualitative risk analysis, any design change and of course the suspension of work due to various reasons. The main tool to manage risks has been attributed to contracts. The risk management policy has to be implied throughout the life of the project. In nutshell, from the initial phase, the contractor and the government bodies should work harmoniously, in coordination so that the potential risks can be addressed well in time.